OPTICAL PROPERTIES OF RAT SERUM AFTER INTRAGASTRIC ADMINISTRATION OF MELANIN - MARTYNIUK, V.; BEREGOVA, T.; TSEYSLYER, Yu.; STEPANOVA, L.; KONDRATIUK, T. (Bulletin of Taras Shevchenko National University of Kyiv. Biology, 2025)
Previous studies of the biological activity of melanin produced by the Antarctic black yeast Pseudonadsoniela brunnea have shown its antioxidant, stress-adaptogenic, dermatotropic, wound-healing and antibacterial effects. However, the primary physicochemical mechanisms of the system influence of melanins remain insufficiently studied. Therefore, the aim of the study was to determine effects of the intragastral administration of melanin produced by the Antarctic black yeast Pseudonadsoniela brunnea on the optical properties of a protein component and an aqueous phase of rat serum. White nonbread adult male rats weighing 180–200 g were used in the experiments. The intragastric route of administration of melanin by means of soft gastric catheter at a dose of 3 mg/kg was used. Rats of the control group were administered the physiological solution in the same way. After 1 hour the animals were sacrificed by cervical dislocation and blood serum was obtained for further studies. The absorption spectra of blood serum samples were recorded using Shimadzu Biospec-Mini spectrophotometer in the range of 190–1100 nm. Analysis of the absorption spectra of blood serum in a wide range from UV to near IR indicated that one hour after intragastral administration of melanin to rats at the dose of 3 mg/kg the optical properties of protein component were not changed, but the properties of the aqueous phase of the blood serum were changed due to statistically significant decrease of an amount of hydrogen bonds. Authors hypothesized that the appearance of substances that destruct the hydrogen bond network in the blood is one of the reasons for such changes. Changes of properties of water as the solvent and the structure-forming factor can have further systemic consequences due to changes in the hydration of biological polymers and low molecular weight metabolites, their solubility and intermolecular interactions, cell membrane permeability, molecular dynamics and functional activity of biomacromolecules, etc.
Keywords: melanin, blood serum, serum proteins, water